The Girl Power of Disney Princesses in Brave and Moana - Angelia Ineke Sumana (Institute of Research and Community Outreach - Petra Christian University, 2022)
In this study, I want to analyze two films called Moana and Brave by Disney Animation. In this film there is a difference in characteristics of a princess who is usually in the field of others, just quiet and waiting for others to help them. That is the reason why I wanted to focus on the main characters named Moana and Merida who have the other side of a princess usually. This thesis talks about the issue of how the characters of Moana and Merida reflect the characteristics of girl power. The thesis aims to show that Moana and Merida can reflect the characteristics of Girl power through their decisiveness, smartness and boldness. In this study, I used girl power theory that Rebecca Walker as pioneer of the third-wave pioneer. As a result, I have found that Moana and Merida reflected the characteristics of Girl power that made them show a new side of the characteristics of a princess that is usually displayed by Disney.Keywords: Disney, Girl Power, decisiveness, smartness, boldness